Clinical, immunologic and virologic outcomes of children and adolescents receiving second line anti-retroviral therapy in two referral hospitals in Addis Ababa, Ethiopia. - Endashaw Tekliye; Tinsae Alemayehu; Tigist Bacha (PLoS ONE, 2021)
Background Ethiopia launched free access for antiretroviral therapy in 2005. The number of patients on second line antiretroviral treatment has increased with each passing year. The objectives of this study were to describe the clinical, immunological and virologic outcomes of children and adolescents receiving second line anti-retroviral therapy in two referral hospitals, Yekatit 12 and Zewditu Memorial Hospitals, in Addis Ababa, Ethiopia. Methods This was a hospital based retrospective cohort study conducted among children and adolescents aged 18 years and less and receiving a second line antiretroviral drugs. Data was collected using structured questionnaires. Means and percentages were used for nominal variables. Statistical analysis was made using statistical software-SPSS 23.0. Kaplan Meier analysis, long rank test and multivariate Cox proportion model were used to identify factors affecting survival. Results A total of 75 children and adolescents were studied with a mean age of 13.28 years (SD: 4) with a mean treatment period on second line regimens of 35.2 months (SD: 21.8 months). Forty-eight participants were experiencing successful measures (in all three parameters) for their second line anti-retroviral treatment. Ten had virologic treatment failure while seven had died. Both treatment failure and death rates were higher within the first two years of treatment. Poor treatment adherence (Adjusted hazard ratio: 5.1 (95% CI: 1.1-23.2; p-value = 0.02)) and advanced World Health Organization clinical stage at start of the second line antiretrovirals (Adjusted hazard ratio: 7.51 (95% CI: 1.35-18.02; p-value = 0.002)) correlated significantly with survival of children and adolescents receiving treatment. Conclusions The study describes clinical, immunological and virologic outcomes of second line antiretroviral treatment in a pediatric cohort under care in two hospitals in Addis Ababa, Ethiopia. Poor adherence and pre-treatment advanced clinical stages were predictors of survival.